Pengaruh Dukungan Keluarga Dan Paritas Terhadap Kecemasan Ibu Hamil Trimester III Dalam Menghadapi Persalinan Di Rumah Bersalin Harapan Bunda Surakarta - Susilowati, Dewi; Suryani, Nunuk; Murti, Bhisma (Jurnal Kedokteran Indonesia, 2012)
Background: Pregnancy yields happiness to pregnant women and their husbands. But it can worry them. The support of family gives pregnant women composure, secure feeling, and comfort thereby reducing pregnant womanâs anxiety. This study aimed to determine the effect of family support and parity on anxiety level among third trimester pregnant women in dealing with delivery. Methods:This analytical observational study usedcross sectional design. The reference population was third trimester pregnant women visiting HarapanBunda Maternal Clinic, Surakarta, from June to July 2012. The independent variableswere family support and parity. The dependent variable was anxiety. The data were analyzed using multiple linear regression model. Results:There were statistically significant effects of family support (b = -0.48; p = 0.017) and parity (b = -3.40; p = 0.007) on pregnant womenâs anxiety in dealing with delivery. Conclusion:Family support and parity reduce anxiety among pregnant women of trimester pregnancy. The stronger the family support the lower is the anxiety of pregnant women. Multipara, on the average, had lower anxiety than primipara. Key words: Anxiety, family support, parity, pregnant woman